Main Characteristics Of The Demographic Situation And Economic And Social Development Of Kashkadarya Region (Eurasian Journal of History, Geography and Economics, 2023)
The article is devoted to the analysis of the socio-economic development of one of the leading regions of the Republic of Uzbekistan - the Kashkadarya region. The features of the modern demographic situation are also considered.